Circulating MicroRNA-92b-3p as a Novel Biomarker for Monitoring of Synovial Sarcoma. Issue 1 (December 2017) - Uotani, Koji; Fujiwara, Tomohiro; Yoshida, Aki; Iwata, Shintaro; Morita, Takuya; Kiyono, Masahiro; Yokoo, Suguru; Kunisada, Toshiyuki; Takeda, Ken; Hasei, Joe; Numoto, Kunihiko; Nezu, Yutaka; et al.
Abstract The lack of useful biomarkers is a crucial problem for patients with soft tissue sarcomas (STSs). Emerging evidence has suggested that circulating microRNAs (miRNAs) in body fluids have novel impact as biomarkers for patients with malignant diseases, but their significance in synovial sarcoma (SS) patients remains unknown. Initial global miRNA screening using SS patient serum and SS cell culture media identified a signature of four upregulated miRNAs. Among these candidates, miR-92b-3p secretion from SS cells was confirmed, which was embedded within tumour-derived exosomes rather than argonaute-2. Animal experiments revealed a close correlation between serummiR-92b-3p levels and tumour dynamics. Clinical relevance was validated in two independent clinical cohorts, and we subsequently identified that serummiR-92b-3p levels were significantly higher in SS patients in comparison to that in healthy individuals. Moreover, serummiR-92b-3p was robust in discriminating patients with SS from the other STS patients and reflected tumour burden in SS patients. Overall, liquid biopsy using serummiR-92b-3p expression levels may represent a novel approach for monitoring tumour dynamics of SS.